Design and Synthesis of Novel Aminoalkanamides Targeting Neurodegeneration and Symptoms of Alzheimer’s Disease - Jankowska, Agnieszka; Satała, Grzegorz; Latacz, Gniewomir; Partyka, Anna; Lubelska, Annamaria; Pociecha, Krzysztof; Świerczek, Artur; Wilczyńska, Natalia; Mordyl, Barbara; Bojarski, Andrzej J.; Wyska, Elżbieta; Chłoń-Rzepa, Grażyna (Current Medicinal Chemistry, 2021)
Background: There is currently no drug that slows the process of neurodegeneration or alleviates the cognitive and depressive symptoms in patients with Alzheimer’s disease. Due to the increasing number of Alzheimer’s patients, there is an urgent need to develop novel drugs with neuroprotective, procognitive, and antidepressant properties. Objective: The aim of this study was to design, synthesize, and evaluate novel aminoalkanamides with serotonin 5-HT1A/5-HT7 receptor affinity and phosphodiesterase (PDE) inhibitory activity as a new approach to combat neurodegeneration and symptoms of Alzheimer’s disease. Methods: The newly designed compounds were synthesized using classical methods of organic chemistry and tested in vitro for their receptor affinity, functional profile, enzyme inhibition, and ADME properties. The neuroprotective effect against H2O2-induced increase of reactive oxygen species level was tested in SH-SY5Y cells. The novel object recognition and forced swimming tests were used to evaluate the procognitive and antidepressant activity, respectively. Results: Synthesized aminoalkanamides were characterized as potent 5-HT1A receptor antagonists with additional 5-HT7 receptor antagonistic properties and PDE4B inhibitory activity. Selected compound 15 showed neuroprotective, procognitive, and antidepressant properties. In addition, compound 15 revealed suitable ADME properties expressed as good membrane permeability and high metabolic stability. Conclusion: This study revealed a new class of compounds that may be useful in the search for an effective drug in the alleviation of neurodegeneration and symptoms of Alzheimer’s disease.
Keywords: aminoalkanamides